Speckle tracking echocardiography in hypertensive males with glucose metabolism disorders - Kolesnyk, M. Yu.; Колесник, Михайло Юрійович (ЗДМУ, 2014)
Aim. Early left ventricle (LV) abnormalities are hardly detectable by means of standard echocardiography in patients with hypertension (HTN) and glucose metabolism disorders. The objective of this study was to assess changes in LV function with speckle tracking echocardiography in hypertensive males with different types of glucose metabolism abnormalities. Methods and results. We recruited 158 hypertensive males with different glycemic status. The multidirectional LV strain was assessed by two-dimensional speckle tracking echocardiography. The patients with HTN and type 2 diabetes mellitus demonstrated signifi cant reduction of LV global longitudinal strain and early diastolic strain rate despite preserved LV ejection fraction. Conclusion. Speckle tracking echocardiography can identify subclinical myocardial alterations in hypertensive males with glucose metabolism abnormalities. Стандартна ехокардіографія не має достатньої чутливості для оцінювання впливу порушень метаболізму глюкози на стан міокарда лівого шлуночка (ЛШ) у хворих з артеріальною гіпертензією. З метою оцінювання можливості ранньої діагностики субклінічного ураження міокарда ЛШ залучили до обстеження 158 чоловіків з артеріальною гіпертензією та різним глікемічним статусом, яким виконали спекл-трекінг ехокардіографію. Встановили, що у хворих на гіпертензію та цукровий діабет 2 типу реєструється вірогідне зменшення глобального поздовжнього стрейну та раннього діастолічного стрейн рейту ЛШ, незважаючи на збережену фракцію викиду ЛШ. Це свідчить про доцільність використання спекл-трекінг ехокардіографії у хворих з артеріальною гіпертензією та порушеннями метаболізму глюкози. Стандартная эхокардиография не обладает достаточной чувствительностью для оценки влияния нарушений метаболизма глюкозы на состояние миокарда левого желудочка (ЛЖ) у больных с артериальной гипертензией. С целью ранней диагностики субклинического поражения миокарда ЛЖ обследовано 158 мужчин с артериальной гипертензией и различным гликемическим статусом, которым выполнили спекл-трекинг эхокардиографию. Установили, что у больных с гипертензией и сахарным диабетом 2 типа регистрируется достоверное уменьшение глобального продольного стрейна и раннего диастолического стрейн рейта ЛЖ, несмотря на сохраненную фракцию выброса ЛЖ. Это свидетельствует о целесообразности использования спекл-трекинг эхокардиографии у больных с артериальной гипертензией и нарушениями метаболизма глюкозы.
Спекл-трекінг ехокардіографія в чоловіків з артеріальною гіпертензією та порушеннями метаболізму глюкози
Спекл-трекинг эхокардиография у мужчин с артериальной гипертензией и нарушениями метаболизма глюкозы
Keywords: Hypertension; Type 2 Diabetes Mellitus; Glucose Metabolism Disorders; Echocardiography; артеріальна гіпертензія; цукровий діабет 2 типу; порушення метаболізму глюкози; спекл-трекінг ехокардіографія; артериальная гипертензия; сахарный диабет 2 типа; нарушение метаболизма глюкозы; спекл-трекинг эхокардиография